The VaMa (Vatavuk and Marić) Artificial Intraocular Lens Capsule: A Novel Device and Method for Reversible Secondary Intraocular Lens Implantation in Patients with Aphakia Without Efficient Capsular Support - Goran Marić; Damir Godec; Bruno Krajačić; Marin Radmilović; Zoran Vatavuk (Biomedicines)
We describe a novel experimental device, the VaMa (Vatavuk and Marić) artificial intraocular lens (IOL) capsule, and a method that enables all IOL types to be implanted in the bag. We present the application of the device and the procedure in patients with aphakia and native capsule damage and without efficient capsular support. The VaMa device and the method facilitate IOL exchange due to refractive errors and, in the case of their invention, the implementation of superior IOLs in the future. The postoperative results after the implantation of the VaMa capsule along with IOLs in three patients are promising, with significant visual improvement and without adverse events 7 to 10 months postoperatively.